Assessment of atrial electromechanical delay by tissue Doppler echocardiography in patients with nonischemic dilated cardiomyopathy - TİGEN, MUSTAFA KÜRŞAT (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2010)
Background: Atrial electromechanical delay (AEMD) calculated from tissue Doppler imaging (TDI) echocardiography can be an alternative to invasive electrophysiologic studies. We investigated whether the AEMD obtained from TDI is prolonged in patients with nonischemic dilated cardiomyopathy (DCM). Methods: Fifty-five patients with nonischemic DCM (23 men/32 women; age, 43.9 +/- 14.8 years) and 55 controls (20 men/35 women; age, 41.3 +/- 13.4 years) were included in this study. Atrial electromechanical delay (the time interval from the onset of P wave on electrocardiogram to the beginning of late diastolic wave [Am wave] on TDI) was calculated from the lateral and septal mitral annulus, and lateral tricuspid annulus (PA lateral, PA septum, and PA tricuspid, respectively). P-wave dispersion was calculated from the 12-lead electrocardiogram. Results: PA lateral and PA septum duration were significantly longer in patients with nonischemic DCM than the controls (78.4 +/- 19.7 versus 53.8 +/- 6.6 and 55.2 +/- 16.3 versus 40.5 +/- 6.2, P < .0001 for both; respectively). However, PA tricuspid duration was statistically similar between the 2 groups (36.4 +/- 10.9 versus 37.2 +/- 5.7, P >= .05). P-wave dispersion was significantly higher in nonischemic DCM patients than the controls (53.0 +/- 14.4 versus 37.5 +/- 5.5, P < .0001). PA lateral was correlated with the left atrial maximal volume (r = 0.64, P < .0001), P-wave dispersion (r = 0.65, P < .0001), and log B-type natriuretic peptide (NT proBNP) (r = 0.63, P < .0001). There was a statistically significant and negative correlation between the PA lateral and left ventricular ejection fraction (r = 0.63, P < .0001) and E-wave deceleration time (r = -0.34, P < .0001). Multivariate analysis revealed that left atrial maximal volume and log NT proBNP were the independent predictors of PA lateral (P < .0001 and P = .003, respectively). Conclusion: The AEMD was significantly prolonged in patients with nonischemic DCM. Left atrial enlargement and log NT proBNP were the independent predictors of this prolongation. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Atrial electromechanical delay; Dilated cardiomyopathy; P-wave dispersion; LEFT-VENTRICULAR DYSFUNCTION; CONGESTIVE-HEART-FAILURE; P-WAVE DISPERSION; NATRIURETIC-PEPTIDE; PROGNOSTIC VALUE; MITRAL-STENOSIS; FIBRILLATION; VOLUME; TIME; PRESSURES